Semeadura direta com espécies florestais nativas para recuperação de agroecossistemas degradados - Santos, Paula Luíza (2010)
The lack of planning in the use of natural resources has resulted into degradation of forest ecosystems found in the state of Sergipe. The study of techniques which aim to revert this degradation scene has major importance to the recovery of these areas. Through this view, this study was focused to evaluate the use of direct seeding and the influence of a physical protector on establishment of native species in two subsystems with different kinds of land occupation located in an agroecosystem in the city of São Cristóvão - SE. The experiment was conducted at the Campus of the Federal University of Sergipe, in a subsystem previously used as grazing and other field with agricultural crops annually. Before the introduction of the direct seeding in field it was conducted in the seed laboratory of the Department of Forest Sciences of the UFS the analysis of physical characteristics and viability of seed lots of species. Four types of pioneer species seeds were used, Erythrina velutina, Bowdichia virgilioides, G. ulmifolia and Machaerium aculeatum, and two climax species, Lonchocarpus sericeus and Sapindus saponaria. The experiment was made in the first week of May 2009, in a randomized of designed blocks, in a factorial scheme with three repetitions. Each specie was sown in a row, with seven plants for each treatment (with and without physical protector), with distance of 1,5x1,5m. The evaluations made in field were: emerging, survival and early development of the species (height, diameter and relative growth rate). Analyzing the influence of plantula emerging and seedlings survival, there was significant difference between the two studied environments, showing better results in the subsystem 2 (agriculture). The use of physical protector influenced on the emerging of plantulas of L. sericeus (50,00%), in the 1 (grazing), and of B. virgilioides (96,19%), in the subsystem 2. For the others species, there is no significant difference with respect to the use or not of the physical protector on the emerging of plantulas. For survival, S. saponaria (90,41%) and L. sericeus (83,95%) had the best results with the use of the physical protector, in the subsystem 1. In subsystem 2, the presence of the physical protector influenced on the survival of B. virgilioides (54,55%) and G. ulmifolia (61,87%). Considering the development of species in the field, E. velutina highlighted among the other species due to the higher values of height and diameter in two subsystems, regardless the absence or not of the physical protector. The use of direct seeding was feasible in the recovery of degraded areas, with the use of native species, in study areas.